Learner Awareness of Recasts in Classroom Interaction: Analysis of Empirical Research in L2 Classroom - Dr. Talal M. Amara (Abhat Journal, 2023)
In the past two decades, there have been a number of research studies that found positive impacts of different types of recasts on learning a range of linguistic forms. This review analyzes the existing empirical research studies about the learners’ awareness of teacher recasts in L2 classroom i¬nteraction. Furthermore, it focuses on the debate about the role of recast in learning a second language. While some researchers have criticized teacher recast as inefficient, unnoticeable, and ambiguous, others have described it as useful and effective in improving learners’ accuracy. Some found that teacher recast may be perceived by learners as a confirmation of meaning rather than form (Lyster, 1998). This review helps pinpoint the factors (i.e. noticeability, learners’ proficiency level, etc.) that contribute to the effec-tiveness of teacher recast. Researchers have yet clearly identified the differ-ential benefits that teacher recast may show in comparison to other forms of corrective feedback